Pengaruh Komunikasi Dan Hubungan Kerja Terhadap Kinerja Karyawan: Literatur Review - Ambarwati Ambarwati; Sri Sundari; Marisi Pakpahan (Manajemen Kreatif Jurnal, 2025)
Performance is the level of achievement and efficiency demonstrated by an employee in carrying out duties and responsibilities at work. Employee performance is measured to what extent he can carry out work that has certain goals and results. The purpose of writing this article is to determine the influence of communication and work relationships on employee performance. Writing this article uses literature study. The method used in this research is qualitative with literature study where the required data is collected through text study, then analyzed using content analysis techniques. Conclusion: Based on the literature study, it shows that from the 6 existing journals it was found that there is a significant influence between communication and work relations on employee performance, where the better the communication and work relations that exist, the better the employee's performance, while the worse the communication and work relations are, employee performance will also worsen where employee performance will affect the performance of a company.